Desmopressin (DDAVP) in the management of patients with congenital bleeding disorders. (12th August 2013) - Leissinger, C.; Carcao, M.; Gill, J. C.; Journeycake, J.; Singleton, T.; Valentino, L.
Summary Bleeding disorders, including haemophilia, von Willebrand disease, and platelet function abnormalities pose a substantial, ongoing management challenge. Patients with these disorders not only require treatment during bleeding events but also need effective management strategies to prepare for events ranging from minor dental procedures to major surgery and childbirth. Moreover, women with bleeding disorders often require ongoing treatment to prevent menorrhagia during childbearing years. Desmopressin (DDAVP), a synthetic derivative of the antidiuretic hormone l‐arginine vasopressin, has become a well‐established tool for the management of patients with bleeding disorders in a variety of clinical settings. However, despite the widespread use of DDAVP, the available clinical evidence on its efficacy and safety in these settings is limited, and there has not been a recent comprehensive review of its role in the clinical management of patients with bleeding disorders. As such, this article provides a review of the mechanism of action and pharmacokinetic properties of DDAVP, followed by a concise summary of the available evidence for its use in the treatment and prevention of bleeding.